Correlation of Family Appraisal with the Ability to Care for Children with Leukemia - Arief, Yuni Sufyanti; Krisnana, Ilya; Rachmawati, Praba Diyan; Kurnia, Iqlima Dwi (International Journal of Psychosocial Rehabilitation, 2020)
Families who have children with chronic conditions such as leukemia, are faced with demands, challenges, emotional and cognitive problems, and changing roles in the family and community. This has an impact on family sustainability in providing care for children. This study aims to explain the correlation between family appraisal and the family’s ability to care for children with leukemia. This study was a correlation study with a cross-sectional design. The population in this study were families with children suffering from leukemia who were treated at Dr. Soetomo Surabaya. A sample of 100 respondents were recruited using a purposive sampling technique with the inclusion criteria being mothers with children suffering from leukemia who receive chemotherapy. Data were collected by questionnaire based on the revised caregiving appraisal scale (RCAS) and the Health Status Questionnaire (HSQ-12). The independent variable was family appraisal while family’s ability (perceived health, personal growth, existential well-being) to care for children suffering from leukemia was the dependent variable. Data were analyzed with Spearman correlation p≤0,05. The results showed a significant relationship between family appraisal (challenge) and personal growth (p = 0.000; r = 0.640), perceived health (p = 0.000; r = 0.536), and existential well-being (p = 0.367; r = -0.091) in treating children with leukemia, whereas the results were different for the relationship between family appraisal (stress) and personal growth (p = 0.002; r = -0.367), perceived health (p = 0.006; r = -0.272), and existential well-being (p = 0.367; r = -0.546). Family Appraisal in caring for children with leukemia is needed by the family so that it can improve the family’s ability to provide optimal care for children with leukemia. Perceived good health, personal growth, and existential well-being of the mother can improve the mother’s ability to care for the child with leukemia. Further research is needed on how the family appraisal model can be used by families caring for children with leukemia.